Journalist questions: comparing adversarialness in Chinese political press conferences. (June 2016) - Du, Xujia; Rendle-Short, Johanna
Abstract: This article examines journalist questions within the context of Chinese political press conferences. The focus of the analysis is on journalistic adversarialness and whether there is measurable difference in the use of adversarial questioning between Chinese journalists and those associated with a free media system. Coding was carried out using a modified version ofClayman et al.׳s (2006) question analysis system, which uses content features and question design to assess the level of question adversarialness. All journalist questions were given a total adversarialness score. Significant differences were found between the level of adversarialness of questions asked by journalists from countries associated with a free media system and Chinese journalists. Cultural and socio-political issues that may provide possible interpretations of these differences are discussed. Highlights: Journalists from free media countries (JFCs) asked more adversarial questions than Chinese journalists in CPPCs. JFCs raised more questions that involve politically controversial topics or attacks on the politician or government. JFCs used various question design techniques to pose adversarial questions.